Assessing Option Grid® practicability and feasibility for facilitating shared decision making: An exploratory study. Issue 7 (July 2015) - Tsulukidze, Maka; Grande, Stuart W.; Gionfriddo, Michael R.
Highlights: We assessed Option Grid ® practicability and feasibility on shared decision making. In simulated consultations clinicians received high scores on information sharing. Preference elicitation and integration were not performed at an optimal level. Use of Option Grids ® did not facilitate optimal levels of SDM competency. Abstract: Objective: To assess the feasibility of Option Grids ® for facilitating shared decision making (SDM) in simulated clinical consultations and explore clinicians' views on their practicability. Methods: We used mixed methods approach to analyze clinical consultations using the Observer OPTION instrument and thematic analysis for follow-up interviews with clinicians. Results: Clinicians achieved high scores on information sharing and low scores on preference elicitation and integration. Four themes were identified: (1) Barriers affect practicability of Option Grids ® ; (2) Option Grids ® facilitate the SDM process; (3) Clinicians are aware of the gaps in their practice of SDM; (4) Training and ongoing feedback on the optimal use of Option Grids ® are necessary. Conclusion: Use of Option Grids ® by clinicians with background knowledge in SDM did not facilitate optimal levels of competency on the SDM core concepts of preference elicitation and integration. Future research must evaluate the impact of training on the use of Option Grids ®, and explore how best to help clinicians bridge the gap between knowledge and action. Practice implications: Clinicians proficiently imparting information in simulations struggled to elicit and integrate patient preferences – understanding this gap and developing strategies to close it are the next steps for implementing SDM into clinical practice.